Duel to the death - Jance, Judith A. (New York, NY Pocket Books, an imprint of Simon & Schuster, Inc., 2018)
After taking down the man responsible for his best friend's death, Stuart Ramey thinks the case is finally closed. That is, until Stu finds himself left with a multimillion dollar fortune in Bitcoins in a desperate bid by Frigg, a rogue AI program created by the killer, to keep itself from being fully deactivated. To sort out his situation and take Frigg down for good, Stu enlists the help of Ali Reynolds and the rest of his cyber security colleagues at High Noon Enterprises. But they are not the only ones who know about Frigg's existence. Graciella Miramar, an unassuming accountant to all appearances, is actually the right-hand woman to El Pescado, the leader of a dangerous drug cartel. She'll do anything to get her hands on that program. With Frigg's help, Graciella hopes to take over her father's criminal underworld and become wealthy beyond her wildest dreams. But Stu--and El Pescado and his henchmen--may not be so easily defeated.
111076
Keywords: Reynolds, Ali -- (Fictitious character); Reynolds, Ali (Fictitious character) -- Fiction; Women private investigators -- Fiction; Artificial intelligence; Arizona -- Fiction; Detective and mystery fiction; Fiction; Thrillers (Fiction); Suspense fiction; Mystery fiction